Antierythropoietin Antibody Production Is Not Associated with Malaria and Malaria-Related Anaemia in Humans - Otchere Addai-Mensah; Daniel Gyamfi; Francis Agyei Amponsah; Max Efui Annani-Akollor; Kwabena Owusu Danquah; Lillian Boateng; Eddie-Williams Owiredu; Edward Y. Afriyie; Richard Vikpebah Duneeh; Renate Asare; David Ofosu Ntiamoah; Richard Boateng (The Scientific World Journal)
Introduction. The pathophysiology of malaria-related anaemia is not fully understood although increased destruction of parasitized and nonparasitized erythrocytes, as well as inadequate erythropoiesis, has been proposed. Circulating antierythropoietin (anti-EPO) antibodies have also been implicated in malaria and malaria-related anaemia in mice. However, studies on this association have not been investigated in humans. This study therefore determined the prevalence of anti-EPO antibody production and assessed its association with malaria and malaria-related anaemia in humans. Methods. A total of 86 children aged 1-10 years (57 children with malaria serving as the case group and 29 healthy children serving as control), all residents of Duayaw Nkwanta, Ghana, were recruited for this case-control study. Venous blood was collected for thick and thin films for malaria microscopy, full blood count by automated haematology analyzer, and antierythropoietin antibody and erythropoietin estimation by sandwich ELISA method. Results. Out of the 86 participants recruited, only 3 (3.5%) were positive for anti-EPO antibody; 2.3% of the case group; and 1.2% of the control group. There was no association between the cases and the controls in the production of anti-EPO antibodies. Erythropoietin concentration was significantly higher in malaria-related anaemic subjects (p=0.032). Conclusion. Antierythropoietin antibodies are not associated with malaria infection and malaria-related anaemia in humans. Erythropoietin concentration is associated with malaria-related anaemia.